2020
DOI: 10.3233/jad-200750
|View full text |Cite
|
Sign up to set email alerts
|

Managing Clinical Trials for Alzheimer’s Disease During the COVID-19 Crisis: Experience at Fundació ACE in Barcelona, Spain

Abstract: Background: The COVID-19 pandemic has brought great disruption to health systems worldwide. This affected ongoing clinical research, particularly among those most vulnerable to the pandemic, like dementia patients. Fundació ACE is a research center and memory clinic based in Barcelona, Spain, one of the hardest-hit countries. Objective: To describe the ad-hoc strategic plan developed to cope with this crisis and to share its outcomes. Methods: We describe participants’ clinical and demographic features. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Four centres 80 , 82 , 85 , 83 published their experiences of the impact of the pandemic on clinical research activities. There was a reduction in patient recruitment and in‐person visits, but participation rates in ongoing studies remained high.…”
Section: Resultsmentioning
confidence: 99%
“…Four centres 80 , 82 , 85 , 83 published their experiences of the impact of the pandemic on clinical research activities. There was a reduction in patient recruitment and in‐person visits, but participation rates in ongoing studies remained high.…”
Section: Resultsmentioning
confidence: 99%
“…Prolonged site closures could also affect participant retention, but, encouragingly, this was not an issue at the Knight ADRC CTU, where we had no attrition of clinical trial participants because of COVID. Other trial sites reported similarly low rates of attrition, such as the Fundacio ACE in Barcelona, where only one partic-ipant out of 108 randomized patients left a clinical trial study during the COVID-19 pandemic (Abdelnour et al, 2020). Anecdotally, we found that participants with symptomatic AD and their caregivers believed they received benefit from participating in blinded randomized trials.…”
Section: Clinical Trials and Clinical Research During The Pandemic: Alzheimer's Disease As An Examplementioning
confidence: 57%
“…We ultimately stopped all in-person visits and had clinical trial staff work from home beginning April 7, 2020, as COVID-19 numbers increased and university guidelines evolved. As at other sites, trial coordinators remained in contact with participants through phone calls, conducting safety assessments and promoting participant engagement (Abdelnour et al, 2020). Clinical trial staff had added administrative burdens during this time, for example, spending time locating and then setting up alternative imaging facilities, working to orient and supervise home health nurses (HHNs), and preparing for remote rather than in-person monitoring.…”
Section: Clinical Trials and Clinical Research During The Pandemic: Alzheimer's Disease As An Examplementioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting point for further study is the potential effects on the gender gap of the application of digital technologies in dementia trials. The COVID-19 pandemic has led to the adaption to a model of care based on digital technologies that will continue into the recovery [ 44 , 45 ]. The use of telemedicine or the application of digitized (at-home) cognitive tests are current technological developments that can benefit the participation of women in trials, as they will avoid recurrent visits to the clinic and thus facilitate family conciliation.…”
Section: Discussionmentioning
confidence: 99%